PP.32.05: DIAGNOSTIC OPPORTUNITIES OF NONINVASIVE TECHNOLOGIES FOR THE DIAGNOSIS OF CORONARY ARTERY DISEASE IN THE 21ST CENTURY. (June 2015) - Tsokolov, A.; Vertelkin, A.; Starikov, V.; Kuzmenko, V.; Patlay, I.
Abstract : Objective: Currently, when performing diagnostic testing for patients with ischemic heart disease and at the subsequent assessment of the data obtained, such situations have arisen when the diagnostic value of the techniques described in the 70–80 s of the 20th century does not correspond to the declared values. In order to clarify this phenomenon there was an attempt to evaluate the sensitivity and specificity of the submaximal cycle ergometer test and 24 h examination Holter electrocardiogram. Design and method: The study included 175 patients (age 61.2 + 8.6 years), who passed coronary angiography during the next month. Average stenotic values of arteries were as follows: for the left coronary artery - 31.3 + 32.3%; right coronary artery - 63, 6 + 35%; circumflex artery - 38.1 + 37.5%; diagonal branch - 15.6 + 28.3%; posterior interventricular branch - 23.8 + 36.4; anterior interventricular artery - 50.8 + 33.8%); achieved during ambulatory ECG monitoring heart rate - 100 + 8.8 beats per min (58.4 + 5.6% of the maximum heart rate of age) without reaching submaximal values (75–80%) of the majority of persons surveyed; ST-segment depression greater than 1 mm was recorded in 31.3% of cases, whereas the real frequency of significant destruction of at least one coronary artery (>50%) was 81.3%. Results: As a result of examination, it was found that the actual sensitivity of the cycle ergometer test is at 40.7% level, specificity is - 76.5%, whereas for a Holter ECG monitoring it is 38% and 100%, respectively (at stenosis of any coronary arteries for more than 50%), which is slightly lower than the values previously described. Probable cause of the discrepancies revealed in the diagnostic value of techniques lies in the change of priorities for the treatment of the underlying disease and comorbidities, as expressed in 1) the capacity of new drugs to affect the NO-dependent vasodilation; 2) the formation of collateral circulation; 3) wider use of statins; 4) intake of prolonged preparations. Conclusions: In light of modern approaches to drug prevention and treatment of cardiovascular disease we should reconsider approaches to Holter ECG monitoring for the purpose of verification of ischemic heart disease, and evaluate the effectiveness of the therapy.